PERSEPSI MASYARAKAT TENTANG ETIKA PELAYANAN PUBLIK PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN PELALAWAN (Studi Kasus di Kelurahan Pangkalan Kerinci Kota) - Hidayah, Nurul; Hambali, Hambali; Haryono, Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the public perception of the ethics of public service in the Pelalawan Regency Population and Civil Registration Service (Case Study in Pangkalan Kerinci Kota). This research was conducted from February to May 2019. The sampling technique was a purposive sampling technique. The sample in this study amounted to 100 people. Data collection techniques used are in the form of observation techniques, interviews and questionnaires. In analyzing data, researchers used a quantitative descriptive method. The results of this study indicate that the percentage of respondents who answered Very Good + Good was 66.80%, where the Good Category was in the range of 50.01-75%. It can be concluded that the public perception of the ethics of public service in the Department of Population and Civil Registration of Pelalawan Regency is in the category of